CAPABILITY OF MULTI SOIL LAYERING (MSL) METHOD IN DOMESTIC WASTEWATER TREATMENT - Resda, Cicilya; Tafaib, Mariana Grace Ustang; Isnani, Shanty; Janah, Solihatun; Wikaningrum, Temmy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2022)
Nowadays, regarding the management of domestic wastewater in the environment, it is very necessary to minimize the occurrence of something that can damage the environment and living things. We solve the problem of how to apply the method in wastewater management, using a comprehensive review of the latest and past literature on the management of domestic wastewater by the multi soil layering method, in addition, there is an evaluation and summary of this article. The purpose of this study was to observe the effect of the Multi Soil Layering (MSL) and permeable layers (zeolite and gravel) method on the efficiency of reducing domestic waste pollutants. From the results of the pollutant parameters analyzed, it shows that the MSL reactor is very effective in reducing the content of pollutants in industrial wastewater to below the efficiency quality standard.